New Perspectives on Cicero's De fato - Bellorio, Fabio (Ciceroniana On Line, 2021)
Part of a rather ample revival of studies of De fato, this article is occupied, in its initial part, with two recently published commentaries on the work, by Hermann Weidemann and Alessandra di Meglio; in particular, reflections on the “Master Argument” are analysed as well as the theory of assent, and so are the proem and the study of confatalia. There follows then an exegetical section, marked by a stylistic and rhetorical approach, with a detailed analysis of the form contra propositum, distinctive of De fato: for one part, this is intended to verify the consistency of the reconstructions thus far alleged by the scholars, who customarily recognized in the scarce philosophical competence of Hirtius the cause of the monologic progress of the treatise; for the other part, an interpretation akin to this character is proposed, keeping in mind a realistic reconstruction both of his speculative interests and of the information that the proem of De fato offers us itself.